2007
DOI: 10.1038/ncprheum0374
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for primary and secondary prevention of Lyme disease

Abstract: Lyme disease (borreliosis) incidence continues to increase despite a growing knowledge of primary and secondary prevention strategies. Primary prevention aims to reduce the risk of tick exposure and thereby decrease the incidence of new Lyme disease cases. Secondary prevention targets the development of disease or reduces disease severity among people who have been bitten by infected ticks. Numerous prevention strategies are available, and although they vary in cost, acceptability and effectiveness, uptake has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Higher levels of knowledge seem to positively influence protective behavior as demonstrated by Gould et al [10]. However, research in areas where LD is endemic has demonstrated that despite adequate knowledge about its symptoms and transmission, many people do not perform behaviors to reduce their risk of infection [25]. These findings suggest that a lack of knowledge is not the only reason for poor uptake of protective behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of knowledge seem to positively influence protective behavior as demonstrated by Gould et al [10]. However, research in areas where LD is endemic has demonstrated that despite adequate knowledge about its symptoms and transmission, many people do not perform behaviors to reduce their risk of infection [25]. These findings suggest that a lack of knowledge is not the only reason for poor uptake of protective behavior.…”
Section: Discussionmentioning
confidence: 99%
“…An antibiotic prophylaxis after a tick bite is not recommended (Corapi et al 2007). Since the majority of patients affected by EM remember a contact with ticks, information of the general population on areas with high incidence and on the clinical presentation of the illness should be provided.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that improved knowledge of the basic protective behaviors that can be taken to reduce tick bites may decrease the risk of tick-borne disease (Ergonul 2006;Mead 2011). Certainly in the case of Lyme disease, our understanding of the tick vector life cycle and the effectiveness of prevention strategies should make it a preventable illness, yet the incidence of the disease continues to increase (Corapi et al 2007).…”
Section: Introductionmentioning
confidence: 99%